Implementación de un sistema de contabilidad en la empresa LIMPIE SAC para mejorar el cumplimiento de sus obligaciones financieras y planificar sus futuras inversiones - Barrueto Huamani, Katherinne Pamela (2019)
The main objective of this research was to implement an accounting system to improve compliance with your financial obligations and plan your future investments. The study was mixed, the interview techniques, surveys and documentary analysis were used to collect the information. The study population consisted on workers in the accounting and financial area of the company Limpie S.A.C. located at Av. Panamericana Sur 273 - Barranco, in Lima, Peru. The data collected were processed and analyzed to solve the problem, regarding the incidence of the implementation of an accounting system to improve compliance with its financial obligations and plan its future investments, it was determined: The company Limpie S.A.C. It does not have control over its overdue invoices receivable and payable, therefore it does not provide income or expenses, it does not have control over these, reaching bank loans on some occasions, that is why there is no real-time knowledge of the economic and financial situation of the company for good decision making.